Beneficial Effect of a Secondary Ligand on the Catalytic Difunctionalization of Vinyl Arenes with Boron and CO2. Issue 23 (14th October 2019) - Perrone, Trina M.; Gregory, Amy S.; Knowlden, Steven W.; Ziemer, Natalie R.; Alsulami, Rabah N.; Petersen, Jeffrey L.; Popp, Brian V.
Abstract: The boracarboxylation of vinyl arenes catalyzed by copper(I) is an alkene difunctionalization reaction that provides synthetically useful β‐boryl‐α‐aryl propanoic acid derivatives. Drawbacks of the original reaction methodology are high catalyst loading and vinyl arene scope limited largely to electron‐rich systems. Herein, we demonstrate that catalytic additives, specifically triphenylphosphine or electron‐rich styrene, leads to improved catalyst efficiency and broadening of substrate scope. With the addition of PPh3, comparable yields of previously reported boracarboxylated substrates as well as two novel β‐boronated non‐steroidal anti‐inflammatory drugs ( bora ‐fenoprofen and bora ‐flurbiprofen) were achieved at lower catalyst loading. Boracarboxylation of electron‐deficient substrates could be achieved through superstoichiometric addition of vinyl arene or addition of secondary phosphine ligand. Reactivity optimization and competition experiments have provided preliminary insights into the ability of PPh3 to aid in the catalytic cycle, specifically carboxylation of electron‐rich benzyl‐copper(I) intermediate. Additional competition studies revealed that a catalytic amount of an electron‐rich vinyl arene could be used in addition to the copper(I) catalyst to promote boracarboxylation of an electron‐deficient styrene derivative. Abstract : Copper catalysis : The boracarboxylation of vinyl arenes is a useful alkene difunctionalization reaction that provides synthetically useful β‐boryl‐α‐aryl propanoic acid derivatives. Here we show that catalytic additives, specifically triphenylphosphine or electron‐rich styrene, leads to improved catalyst efficiency and broadening of substrate scope. Preliminary experiments are described that begin to clarify the role of ligand additive in the catalytic reaction.